Social support and posttraumatic stress disorder among flood victims in Hunan, China - Shuidong, F.; Hongzhuan, T.; Abuaku, B.K. (Annals of Epidemiology 17(10): 827-833, 2007)
Purpose: To explore the relationship between social support and posttraumatic stress disorder (PTSD) among flood victims. Methods: A cross-sectional survey was carried out in 2000 among individuals who had suffered floods in 1998 in Hunan, China. Multistage sampling was used to select the subjects from the flood-affected areas. PTSD was diagnosed according to DSM-IV criteria, and social support was measured according to a social support rating scale. Data were collected through face-to-face interviews using a structured questionnaire. Multiple logistic regression analysis and confirmatory factor analysis was used to examine the relationship between social support and PTSD. Results: Out of a total of 25,4 78 subjects interviewed, 2336 (9.7%) were diagnosed as having PTSD. PTSD was significantly associated with total social support (odds ratio [OR] 0.80, 95% confidence interval [CI], 0.78-0.82), subjective support (OR 0.48, 95%CI, 0.44-0.52), and support utilization (OR 0.53, 95%CI,0.49-O.57). Conclusion: PTSD in flood victims is significantly associated with social support; subjective support and support utilization may play more important roles in mitigating the impact of flood than objective support.
Keywords: Floods; Posttraumatic Stress Disorder; Social Support; Epidemiology